Recurrence‐free survival dynamics following adjuvant chemotherapy for resected colorectal cancer: A systematic review of randomized controlled trials - Emma Vail; Ankur P. Choubey; H. Richard Alexander; David A. August; Abril Berry; Patrick M. Boland; Mariam F. Eskander; Miral S. Grandhi; Brittany Haliani; Haejin In; Timothy J. Kennedy; Russell C. Langan; et al. (Cancer Medicine, 2024)
Abstract Background Several cytotoxic chemotherapies have demonstrated efficacy in improving recurrence‐free survival (RFS) following resection of Stage II–IV colorectal cancer (CRC). However, the temporal dynamics of response to such adjuvant therapy have not been systematically quantified. Methods The Cochrane Central Register of Trials, Medline (PubMed) and Web of Science were queried from database inception to February 23, 2023 for Phase III randomized controlled trials (RCTs) where there was a significant difference in RFS between adjuvant chemotherapy and surgery only arms. Summary data were extracted from published Kaplan–Meier curves using DigitizeIT. Absolute differences in RFS event rates were compared at matched intervals using multiple paired t‐tests. Results The initial search yielded 1469 manuscripts. After screening, 18 RCTs were eligible (14 Stage II/III; 4 Stage IV), inclusive of 16,682 patients. In the absence of adjuvant chemotherapy, the greatest rate of recurrence was observed in the first year (mean RFS event rate; 0–0.5 years: 0.22 ± 0.21; 0.5–1 years: 0.20 ± 0.09). Adjuvant chemotherapy was associated with significant decreases in the RFS event rates for the intervals 0–0.5 years (0.09 ± 0.09 vs. 0.22 ± 0.21, p < 0.001) and 0.5–1 years (0.14 ± 0.11 vs. 0.20 ± 0.09, p = 0.001) after randomization, but not at later intervals (1–5 years). In Stage IV trials, RFS event rates significantly differed for the interval 0–0.5 years (p = 0.012), corresponding with adjuvant treatment durations of 6 months. In Stage II/III trials, which included therapies of 6–24 months duration, there were marked differences in the RFS event rates between surgery and chemotherapy arms for the intervals 0–0.5 years (p < 0.001) and 0.5–1 years (p < 0.001) with smaller differences in the RFS event rates for the intervals 1–2 years (p = 0.012) and 2–3 years (p = 0.010). Conclusions In a systematic review of positive RCTs comparing adjuvant chemotherapy to surgery alone for Stage II–IV CRC, observed RFS improvements were driven by early divergences that occurred primarily during active cytotoxic chemotherapy. Late recurrence dynamics were not influenced by adjuvant therapy use. Such observations may have implications for the use of chemotherapy for micrometastatic clones detectable by cell‐free DNA‐based methodologies.